Seasonal Variation in Mulberry Leaf Composition and its Effect on Silk Worm Rearing - Shukla, P. (Indian Forester, 1964)
Mulberry leaf samples were collected every month from selected mulberry bushes at the Government Central Silk Farm, Premnagar, Dehra Dun and analysed separately. Analytical data of leaf showed a decreasing tendency in nitrogen, phosphorus and potassium contents from leaf-bud-opening to leaf-fall stage while calcium, silica and ash percentage have increased. These variations in the mulberry leaf composition may be attributed as one of the factors responsible for deterioration of leaf quality for silk worm during autumn crop and consequently resulting in a low cocoon yield percentage as compared to that of spring crop. Yellowing of leaves and their fall in winter may be due to these seasonal changes in mulberry leaf composition. Hence in order to ensure a good autumn rearing crop, adequate amount of nitrogenous, phosphatic and potassic fertilizers must be applied to the mulberry plantations meant for silk worm rearing.